PENGARUH PUASA INTERMITEN MENGGUNAKAN METODE PUASA DAUD TERHADAP KADAR SGOT TIKUS PUTIH (Rattus norvegicus) ALIRAN WISTAR YANG DIINDUKSI PARACETAMOL - Dagradi, Eric Mayo; Sukmana, Judya; Rahayu, Indri Ngesti (Fakultas Kedokteran, Universitas Hang Tuah, 2022)
Background: Intermittent fasting is done with one day of fasting and one day of eating as usual so that it can reduce oxidative stress, inhibit apoptosis and tissue damage which will reduce degenerative diseases. Fasting can activate SIRT1 and SIRT3 to prevent apoptosis by decreasing reactive oxygen species and inhibiting the mitochondrial permeability transition pore component. The accumulation of free radicals is one of the mechanisms that play a role in liver damage so that the SGOT enzyme present in the liver cells will leave and enter the blood circulation, so that the number of these enzymes in the blood increases. Objective : To prove that there was a decrease in the levels of SGOT (Serum Glutamic Oxaloacetic Transaminase) in male white rats (Ratus norvegicus) of the wistar strain which were fasted intermittently by the Daud fasting method after being induced by Paracetamol. Method : The research design used is a laboratory experimental research type where the method used is randomized the post only control group design. The experimental animals used were white rats (Rattus norvegicus) wistar strain 2-3 months old with an initial body weight of 150-200gr as many as 32 tails. During the fasting treatment, the research subjects were not given diet and drinking, while the non-fasting subjects were given a standard diet and drank regularly were divided into four groups, namely negative control with a water probe that was filtered for 10 days and 1ml of 1% CMC-Na, positive control with a probe. filtered water for 10 days and induction of paracetamol 400mg/kgBW, treatment 1 with standard diet and induction of paracetamol and treatment 2 with intermittent fasting and induction of paracetamol. Results: The results of this study indicate that One-Way ANOVA test obtained p value = 0.384. (p > 0.05) then H0 was accepted, there was no significant difference between the SGOT levels of the experimental animal group that was given a standard diet, the experimental animal group that was given intermittent fasting, the experimental animal group that was given a standard diet and paracetamol and the experimental animal group that was given intermittent fasting and paracetamol treatment. Conclusion: There is no effect of intermittent fasting with the Dawood fasting method on decreasing SGOT levels in male white rats (Rattus norvegicus) Wistar strain induced by paracetamol. Keywords: intermittent fasting, SGOT, paracetamol